2021
DOI: 10.3390/ijerph182211798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Isolated Soy Protein Supplementation Combined with Aerobic Exercise Training on Improving Body Composition, Anthropometric Characteristics and Cardiopulmonary Endurance in Women: A Pilot Study

Abstract: Today, women are concerned with health promotion but also with improvements in body weight and shape. The purpose of this study was to investigate the effects of aerobic exercise training (AET) combined with isolated soy protein (ISP) supplementation on the body composition, anthropometric characteristics, and cardiopulmonary endurance of women. The qualified subjects were randomly assigned to AET or AET + ISP groups. Women in the AET + ISP group were given an ISP-rich supplement (40 g/day) 5 days a week for 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…No differences between groups were observed for lean mass. In contrast, Li et al [37] reported that an eight-week low-to-moderate AT program combined with isolated soy protein supplementation increased lean mass, but not physical performance in young women. Fairbairn et al [38] did not observe significant improvements in mobility in older women who adhered to a 24-week AT program plus docosahexaenoic acid supplementation.…”
Section: Discussionmentioning
confidence: 87%
“…No differences between groups were observed for lean mass. In contrast, Li et al [37] reported that an eight-week low-to-moderate AT program combined with isolated soy protein supplementation increased lean mass, but not physical performance in young women. Fairbairn et al [38] did not observe significant improvements in mobility in older women who adhered to a 24-week AT program plus docosahexaenoic acid supplementation.…”
Section: Discussionmentioning
confidence: 87%